2017
DOI: 10.1002/pen.24780
|View full text |Cite
|
Sign up to set email alerts
|

Excellent toughness, crystal morphology and crystallization mechanism of transcrystallization of polypropylene induced by layered interface

Abstract: The performances of isotactic polypropylene (iPP) have always been related to its crystal morphology and structure. In this work, β‐transcrystallization (β‐TC) was obtained by constructing iPP and β‐nucleated iPP (β‐iPP) multilayered structures. By changing the number of layers, the β‐TC content in layered samples was controlled. During the isothermal crystallization at 130°C, the β‐nucleating agents induced β‐spherulites in β‐iPP layers, then the β‐nucleus at the interface induced the formation of β‐TC which … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 46 publications
(52 reference statements)
0
1
0
Order By: Relevance
“…Materials with multilayer alternated structure were first found in natural shells. Inspired by such unique structure, some work paid attention to studying the effect of multilayer alternated structure on the comprehensive properties to provide guidance for the preparation of novel polymer materials. The results showed that materials with such unique structure not only manifest high strength, modulus, but also excellent impact toughness. It is also found that the interfacial adhesion strength of multilayer alternated materials plays an important role on the enhancement of its mechanical properties.…”
Section: Introductionmentioning
confidence: 99%
“…Materials with multilayer alternated structure were first found in natural shells. Inspired by such unique structure, some work paid attention to studying the effect of multilayer alternated structure on the comprehensive properties to provide guidance for the preparation of novel polymer materials. The results showed that materials with such unique structure not only manifest high strength, modulus, but also excellent impact toughness. It is also found that the interfacial adhesion strength of multilayer alternated materials plays an important role on the enhancement of its mechanical properties.…”
Section: Introductionmentioning
confidence: 99%